PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS IX SMP NEGERI 1 TANJUNG MORAWA - Edita Simanjuntak; Dermauli Sitorus (Jurnal Dedikasi Pendidikan, 2021)
This classroom action research aims: 1) To determine the application of the Cooperative Script learning model in increasing student learning interest 2) To determine the increase in students’ understanding in increasing students’ interest in learning through the application of the Cooperative Script learning model; 3) How do the students’ responses in learning Bahasa Indonesia. The material was the understanding of short story building elements through the application of the Cooperative Script learning model. The research was conducted using interactive qualitative methods and Class Action Research which was conducted in 2 cycles. Each cycle included planning, implementation, observation and reflection. The research subjects are students of class IX odd semester SMP Negeri 1 Tj.Morawa, Deli Serdang Regency. The results of the study for students' initial conditions as measured by a written test and the results of classroom action research with 2 cycles, showed an increase in the learning outcomes achieved by students in mastering the material. Based on the data analysis, it can be concluded that in cycle 1 the students' learning completeness on this material was only 69.29, while in cycle 2 by applying the Cooperative Script learning model increased in cycle 2 the average value increased to 87.14. Student response also increased, data from observations of student activity from 62.50% in cycle 1, increased in cycle 2 to 85.42%.